1961
DOI: 10.1084/jem.114.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Triton Hyperlipemia in Dogs

Abstract: In a previous paper (1) it was shown that triton WR-1339, I a non-ionic surface-active agent, produces, in vitro, notable physical and chemical changes of serum lipoproteins and chylomicrons. I t was assumed that if similar alterations occurred in vivo, they might be partially responsible for the hyperlipemia that had been described in rabbits (2), guinea pigs (2, 3), mice (4), and rats (5) following administration of the detergent. To test this assumption, 14 dogs were given prolonged intravenous treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…The involvement of the reticulo-endothelial system in dogs receiving Triton WR-1339 has been documented. 13 In those studies, a marked accumulation of lipid-laden macrophages in the spleen, liver, lymph nodes, and arteries was observed after the chronic administration of Triton. Still used electron microscopy to demonstrate 40 the presence of Triton-lipid complexes in the endothelium of the arterial intima in rats and rabbits given several intravenous injections of Triton WR-1339.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The involvement of the reticulo-endothelial system in dogs receiving Triton WR-1339 has been documented. 13 In those studies, a marked accumulation of lipid-laden macrophages in the spleen, liver, lymph nodes, and arteries was observed after the chronic administration of Triton. Still used electron microscopy to demonstrate 40 the presence of Triton-lipid complexes in the endothelium of the arterial intima in rats and rabbits given several intravenous injections of Triton WR-1339.…”
mentioning
confidence: 90%
“…Based on past and current studies in this laboratory 12 ' 13 and studies by Ishikawa and Fidge, 15 we can state that the early Triton lesion is confined to the HDL class, which is known to play several functional roles in lipid metabolism. 18 In this context, Triton WR-1339 appears to be a very useful probe for studying the structure and function of HDL both in normo-and hyperlipidemic animals.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The increase of WBC counts in rats with severe hyper lipidemia induced by 300 mg/ kg of T-WR might be explained by an inflammatory reaction such as an acute phase reactive response. Furthermore, large amounts of T WR may have altered the permeability of the vascular endothelium and/or the vascular smooth muscle through a direct combination of the detergent with the lipoprotein lipids of the cell membranes (31). These results indicate that the intravenous injection of 200 mg/kg of T-WR is suitable for the experi mental model of hyperlipidemia in rats.…”
Section: Discussionmentioning
confidence: 85%
“…In fact, we observed hematuria, hamafecia and hemolysis in some rats treated with 300 mg/ kg of T-WR. Scanu et al reported that the osmotic fragility of the red cells increased proportionally to the amount of T-WR employed (31). Since T-WR as a detergent has a hemolytic side effect, large doses of T-WR might induce the decrease in RBC counts and Hb values.…”
Section: Discussionmentioning
confidence: 99%